Permainan ULTAJAS (Ular Tangga Jajanan Sehat) Terhadap Peningkatan Pengetahuan Anak Tentang PJAS (Pangan Jajanan Anak Sekolah): Permainan ULTAJAS (Ular Tangga Jajanan Sehat) Terhadap Peningkatan Pengetahuan Anak Tentang PJAS (Pangan Jajanan Anak Sekolah) - inayah, Ade; Nurul Rohimah, Sri; Fitri, Amelia; Siti Sopiah, Sopa; Salsabila, Siti Sumiati; Nur Amanah, Siti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: PHBS is an effort to provide learning experiences that create conditions for individuals, families and groups by opening lines of communication, providing information and providing useful education to increase knowledge and attitudes regarding clean and healthy living behavior through approaches, creating an atmosphere and empowering the community. Objective : to increase children's knowledge about healthy and nutritious snacks and make efforts to reduce the malnutrition status of healthy and unhealthy snacks. Method:  Health education methodology that includes self-health. Participants in this consultation are expected to be able to implement a comprehensive strategy, especially in creating new behaviors, especially PHBS, in the school and community environment. Result: From the results of the study it can be concluded that before delivering the health consultation material as many as 2 people (0.3%) were able to answer questions before the material was delivered, 3 people (0.5%) did not know. Participants did not know about healthy snacks, 1 person (0.2%) participants did not know, participants did not know about healthy snacks. After health counseling, the knowledge of PHBS healthy snack participants increased 100% to 6 people. Conclusion: Expanding knowledge about healthy snacking is a great start for teaching clean and healthy living habits in everyday life. After knowing the characteristics of unhealthy snacks and the dangers of unhealthy snacks, it is hoped that children will stop buying unhealthy snacks.